FORMULASI RODENTISIDA NABATI PAPAIN PEPAYA (Carica papaya L.) SEBAGAI ALTERNATIF PENGENDALI MENCIT - Nova Pramestuti; Corry Laura Junita Sianturi; Bina Ikawati; Agus W Anggara (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2018)
Rats as reservoirs of zoonotic diseases. Rodenticides are commonly used for control of rats. They can beextremely harmful to humans, not only kill rats and other rodents, but also kill their predators. Therefore, usingnatural rodenticide may be a better alternative. Combination of papain and salt can kill rats more quickly. Theaim of this study was to make a proportion of natural rodenticide appropriately to control mice with papain asactive ingredient. A quasi-experiment with post-test only with control group design was used in the study. There were four treatment used in this study i.e treatment A (papain 16%), B (papain 24%), C (papain 32%), and D (papain 40%). Each was mixed with corn, wheat, soy, caramel, papain product for the brand “X” (consist ofpapain, salt, sugar), paraffin, corn oil and refined sugar. Rodenticides given to mice for seven days, feed intakeand death of mice were observed every day. The results showed that mice death were decreased in corcondantwith increasing the concentration of papain product for the brand “X”, after rodenticide treatment. There is asignificant difference in mortality rate of mice among various rodenticide formulations (p-value<0.05), withthe most significant differences in treatment A and D. Feed proportion which contains papain product for thebrand “X” 40% can be used as an alternative to make natural rodenticide with the highest mortality.